1987
DOI: 10.1002/1097-0142(19870801)60:3<280::aid-cncr2820600303>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Elective postoperative external radiotherapy after hysterectomy in early-stage carcinoma of the cervix. Is additional vaginal cuff irradiation necessary?

Abstract: This retrospective study of 44 patients who received postoperative radiotherapy soon after hysterectomy for early Stage IB to IIA carcinoma of the cervix was undertaken to determine the need for additional vaginal cuff irradiation (AVCI) following external pelvic irradiation (EPI). The reasons for adjuvant radiotherapy administration were mostly the nonradical type of performed hysterectomy or the presence of adverse prognostic histopathologic features. The overall survival and local control rates were 80% (35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Eleven of the 26 patients in our study had prognostic high risk factors in the primary situation but had not undergone postoperative pelvic irradiation for various reasons. Adjuvant radiotherapy in case of risk factors has been the usual clinical practice for early cervical carcinoma in many departments [2,12,19,33,39,45]. Many authors emphasize the value and necessity of adjuvant treatment in patients with high risk factors [4,20,26,37] like positive pelvic lymph nodes, parametric involvement, positive margins, lymph-or hemangiosis, bulky tumors, deep invasion of cervical stroma, or histology of adenocarcinoma, clear-cell or small-cell carcinoma [1,3,7,10,15,16,27,31,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the 26 patients in our study had prognostic high risk factors in the primary situation but had not undergone postoperative pelvic irradiation for various reasons. Adjuvant radiotherapy in case of risk factors has been the usual clinical practice for early cervical carcinoma in many departments [2,12,19,33,39,45]. Many authors emphasize the value and necessity of adjuvant treatment in patients with high risk factors [4,20,26,37] like positive pelvic lymph nodes, parametric involvement, positive margins, lymph-or hemangiosis, bulky tumors, deep invasion of cervical stroma, or histology of adenocarcinoma, clear-cell or small-cell carcinoma [1,3,7,10,15,16,27,31,34].…”
Section: Discussionmentioning
confidence: 99%
“…If paraaortic lymph node metastases existed, they were treated with 46/50.4 Gy (single dose 2/1.8 Gy). (6) Positive pelvic lymph nodes (5) of the pelvic wall (16) Bulky disease (> 3.5 cm) (2) • Vagina ± paravaginal Parametric involvement (6) tissue only (7) • With infiltration of the wall of rectum or bladder (4) • With infiltration of the lymph nodes (5) -Iliac lymph nodes (1) -Iliac and inguinal lymph nodes (1) -Iliac and paraaortic lymph nodes (3) Central with infiltration of the pelvic wall (10) • Without lymph nodes (9) • With lymph nodes (1) In total, a dose of 55-65 Gy was delivered to the site of recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…Ampil et al [9] described results in 44 patients who received post-operative irradiation after hysterectomy for stage IB or IIA cervical cancer (15 patients were treated with radical hysterectomy). They suggested that the combination of external radiation with additional vaginal cuff irradiation is recommended for patients treated with simple hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Dans une étude sur 90 patientes traitées par radiothérapie après hystérectomie simple inadaptée (cancer du col de stades Ib à IIb), Hsu retrouve un taux de complications tardives de 15,5 %, dont seulement 1 % nécessitant une prise en charge chirurgicale [41]. L'intérêt d'associer une curiethérapie à la radiothérapie externe est discuté par certains auteurs qui attirent l'attention sur une augmentation du taux de complication sans bénéfice thérapeutique évident [21,34,43]. Pour l'approche chirurgicale, le taux de complication peropé-ratoire (plaies viscérales, transfusions) varie de 5,5 à 35 % et le taux de complication à long terme (troubles urinaires essentiellement) de 0 à 8,7 % [14][15][16][17].…”
Section: Discussionunclassified